Path planning, re-planning and traversal in real-time dynamic environments - Inventado, Paul Salvador B. (Animo Repository, 2007)
This paper discusses a path planning approach in a real-time dynamic environment, specifically, in a Role Playing Game (RPG) entitled DIGMA. In DIGMA, Path planning is used to control the movements of agents or characters within the game. This domain is a real-time game, thus requiring path planning in real-time. At the same time, it contains dynamic elements which require it to adapt to changes in the course of planning. The approach used in the domain is first discussed and the results gathered after applying them are explained.